Scoring System for Screening Fitness to Work for Offshore and Onshore Remote Area Worker - Kamal, Kasyunnil (Occupational and Environmental Medicine Journal of Indonesia, 2025)
Background: About 10-15% of medical examinations of workers at upstream oil and gas companies are not conducted properly. In some cases, workers die at worksites. Many doctors carrying out the assessment lack the competency to assess occupational risks. In this study, we developed a scoring system for ‘fitness for work’ assessment, which can be used by trained doctors. Methods: Diagnostic testing was done with comparing the results of the determination screening fitness for work using a scoring system with the determine fitness for work results by Occupational Medicine Specialist as a gold standard in the same group. The entire 607 samples used in this study. The development of the scoring system for ‘fitness for work’ assessment used the Delphi method. This scoring system consists of three variables, i.e. health status, occupational risks, and referral time. ’Fitness for work’ status were determined by summing up the score from each variable and then compared with the gold standard. The outcome of this study are the sensitivity, specificity, positive predictive value, and negative predictive value of the scoring system. Results: The scoring system conducted by general practitioners in this study showed high sensitivity (98.8%), positive predictive value (99%), and specificity (79%). Conclusion: A scoring system based on health condition, occupational risks, and referral time can be used by doctors working in upstream oil and gas companies to assess ‘fitness for work’ of their offshore or remote onshore employees.